Intra-articular Corticosteroids for Osteoarthritis of the Knee - da Costa, Bruno R; Hari, Roman; Jüni, Peter (JAMA : the journal of the American Medical Association, 2016)
CLINICAL QUESTION: Are intra-articular corticosteroids associated with improvement in pain and physical function compared with sham injection or no intervention in patients with knee osteoarthritis? BOTTOM LINE: Intra-articular corticosteroids may be associated with moderate improvement in pain and a small improvement in physical function up to 6 weeks after injection. However, the quality of the evidence is low.